Cutaneous cytomegalovirus in mixed serostatus kidney transplant patient - Dominic Finan; Vaibhav Garg; Lucjan Lang; Tricia Royer; Katherine Belden; Sherry Yang (SAGE Open Medical Case Reports)
Cutaneous cytomegalovirus infection is a rare but serious complication in solid organ transplant recipients. We present a 47-year-old male kidney transplant recipient with a chronic, nonhealing right lower extremity ulcer. Initial biopsies revealed septic vasculopathy, leading to treatment with sodium thiosulfate and antibiotics for suspected calciphylaxis. Despite regular wound care, the ulcer continued to worsen. After completing 6 months of cytomegalovirus prophylaxis, surveillance viral levels remained undetectable, but the ulcer progressed considerably. Worsening severity prompted hospitalization, during which cytomegalovirus viremia was detected, and an ulcer biopsy confirmed cytomegalovirus inclusion bodies. Antiviral therapy was reinitiated, resulting in rapid and sustained wound improvement. Therefore, this case underscores cytomegalovirus’ potential for cutaneous invasion in transplant recipients, even without preceding viremia, and highlights the importance of considering cutaneous cytomegalovirus in nonhealing ulcers posttransplant, especially in serodiscordant recipients.